PELATIHAN PUBLIC SPEAKING UPAYA MENINGKATKAN PEMBERDAYAAN MASYARAKAT DESA SEI BELURU UNTUK MENCAPAI KUALITAS BERKOMUNIKASI LEBIH BAIK DI ERA 5.0 - Susi Masniari Nasution; Bambang Gulyanto; Eka Oktavia Anzani; Ruri Syahmida Sinaga; Cici Vira Puspita; Alda Tiyana Sinaga; Lisa Aulia; Lili Indra Aprilia (Smart Education, 2024)
The main problem which was faced by Indonesian people, especially in the field of education and globalization, is the low level of quality of human resources. One of the efforts to improve the quality of human resources is to develop an interest in reading like reading habits as well as having polite speech. Public speaking or public speaking skills are very beneficial for children in the process of self-development. However, many children feel less confident, don't master the material, or don't understand how to do it. Children's public speaking skills must be nurtured, trained and developed continuously. These conditions became the basis for implementing the Community Service (PKM) program which was attended by 19 students who joined Sei Beluru Village. The PKM program is packaged in the form of training with the aim of building confidence in speaking in public, understanding the material to be presented, and being able to apply public speaking techniques. The training was held on Thursday 03 October 2024 at the Sei Beluru Village Hall Office. Implementation starts from the initial observation stage, orientation, introduction to material, practice, and ends with evaluation. The results of the training were quite good, it was proven that after delivering the material, the participants had achieved adequate public speaking skills, their self-confidence had increased even though it was still doubtful (nervous) , able to present the material that had been presented well, and were able to apply the public speaking techniques.The Keywords: face to face learning; implementation; procedures; strategy; training